Current Status of Cold Chain Equipment: A Guarantee of Carbon Footprint Reduction from Food Waste to a Sustainable Environment - Eric, Kasamba Ilunga (Research Advances in Environment, Geography and Earth Science Vol. 7, 2024)
The cold chain is vital for reducing food waste and ensuring food safety. The installation, monitoring and maintenance of cold chain equipment would play a vital role in ensuring healthy food quality and reducing losses and pollution. The objective of this work was to evaluate the current status of commercial cold chain equipment primarily, and secondarily to determine elements associated with the management of cold chain equipment. To achieve this, a cross-sectional descriptive study began on August 7 to September 23, 2023, covering 84 commercial establishments including supermarkets, delicatessens and butchers, food, and butchers in the city of Lubumbashi. The data were collected by interview and direct cross-sectional observation on the evaluation of the conservation of frozen products (fish, meat, and cold meats) on the market in the city of Lubumbashi. To assess the quality of all included studies, two analysts independently assessed the quality of the included data by checking the completeness of the inclusion criteria. The results show us that the structures using cold chains are food stores, butchers, delicatessens, and supermarkets and sometimes in a certain combination. All these structures mainly use freezing and sometimes refrigeration to maintain the cold chain. Equipment such as cold chain freezers, quick freezers, refrigerated cabinets and refrigerators and insulated boxes are all the equipment used for this purpose, powered by the supply of electric current throughout and often using generators and rarely solar panels in the event of an outage of electric current. Thus, these structures operate in an environment rich in temperature fluctuations leading to rapid deterioration of food, waste, responsible for 4% of global greenhouse gas emissions GHG, the equivalent of the contribution of the entire African continent to climate change. Reducing food waste requires the commitment of all countries in the world to combat food waste, must take measures in terms of laws, systems and policies in order to develop an appropriate strategy for reducing food loss and waste is one of the important issues related to sustainable development. This work demonstrated the importance of the quality of cold chain equipment on food quality and its impact on the carbon footprint, a situation observable from the production, transport, storage, and elimination of food. The use of solar energy would be a solution in this process because it produces less greenhouse gases.